What's the story? The effects of narratives in science classrooms - Leipzig, Peter, author; Balgopal, Meena, advisor; Ode, Paul, advisor; Doe, Sue, committee member; Knapp, Alan, committee member (Colorado State University. Libraries, 2018)
While effective science communication is crucial, it also presents multiple obstacles for natural science researchers and specialized communicators. This includes a language divide between scientists and the general public, making science less approachable to novices. The use of narratives within science represents a powerful strategy for overcoming these issues. We examined the reported effects of narratives as a communication strategy and reviewed the varying definitions of narratives in the literature. We propose a set of essential elements that differentiate narrative communication from other forms, all of which are useful for researchers seeking to understand the impacts of stories. These elements include events, characters, causality/agency, and conflict/resolution. We also studied the effects of training graduate teaching assistants (GTAs) using narrative communication. We examined i) what narrative elements GTAs incorporated into their own lessons, ii) why they chose to include stories in their classes, and iii) how training affected content knowledge and self-perceptions for GTAs and their undergraduate students. We found that GTAs who were trained using stories were more likely to integrate the narrative elements into their lessons. Additionally, when employing narratives, GTAs focused on the process of science rather than the results. However, the GTAs did not demonstrate or perceive any concrete knowledge gains. Finally, we argue that narratives can and should be incorporated into more introductory courses across multiple disciplines.